THERMAL SYNTHESIS OF AMINO ACIDS AND THE ORIGIN OF LIFE - Fox S.W. (My University, 1995)
The recent review by Marshall (1994) of the production of amino acids from the interstellar components, formaldehyde and ammonia, is placed in the larger context of the origin of life. Thermal energy, being ubiquitous in the Earth, emerges as the sole necessary form of energy. To appreciate the overview of the natural evolutionary sequence it is necessary to recognize stepwiseness in evolution, a principle that has however been often ignored. Since self organization of thermal protein to cells is instantaneous, but only one step in a geochemical ladder, individual steps may be regarded as instantaneous, while the sequence requires measurable time. Two steps indicated are extrusion of a hot, dry organic magma of amino acids -> peptides into an aqueous environment in which occurs a second step of self organization. In this paper, spinoffs of the defensible theory for the origin of life have been briefly reviewed as a fundamental consequence of nonrandom thermal copolymerization of amino acids.